Role of kidney transplantation in long-term cardiac reverse remodeling and interconnecting mechanisms in type 4 cardiorenal syndrome - Salas-Pacheco, Jose Luis; Arreola-Guerra, Jose Manuel; Marquez-Velasco, Ricardo; Perez-Torres, Israel; Casarez-Alvarado, Sergio; Fuentevilla-Alvarez, Giovanny; Guarner-Lans, Verónica; Cruz-Soto, Randall; Soto, María Elena (Frontiers in Nephrology, 2025)
BackgroundType 4 cardiorenal syndrome (CRS) involves cardiovascular alterations caused by chronic kidney disease (CKD). Fibroblast growth factor-23 (FGF23), carboxy-terminal propeptide of procollagen type I (PIP), and parathyroid hormone (PTH) have been proposed as biomarkers of pathological cardiac remodeling in CKD. In contrast, it has been suggested that MicroRNA 221 has a cardioprotective role. Available evidence shows that, 12 months after kidney transplantation (KT), type 4 CRS reverts in only half of the patients.ObjectiveTo assess long-term cardiac reverse remodeling after KT and its association with FGF23, PIP, and PTH levels.MethodsPatients with end-stage renal disease were assessed before and 28 months after KT using FGF23, PIP, and PTH serum concentrations and transthoracic echocardiography.ResultsFifty-three patients were followed for 28 months after KT. All the patients showed cardiac abnormalities upon inclusion. A follow-up assessment showed a reduction in left ventricle (LV) mass (121 ± 48 vs. 65 ± 14 gr/m2) and left atrial volume (46 vs. 30 ml/m2). The LV ejection fraction (53 vs. 63%), LV global longitudinal strain (-15.9 vs.-19.4%), and LV diastolic function improved. miR-221 expression increased after KT (8.73 RIQ= 3.7-25 vs. 40.16 RIQ= 24-223, p=0.001) and was correlated with the Ee´ratio (r= -0.32, p= 0.02). Multivariate analysis showed that post-KT LV mass was determined by pre-KT LV mass, serum Cr level, post-KT PIP, and hypertension (R2 = 0.65, F=12.1, p=0.001).ConclusionsContrary to other evidence, this study demonstrated that type 4 CRS is reversible over the long term. This is a paramount finding because KT normalizes cardiac structure and function independently of the severity of basal cardiac abnormalities.